Aerobic Synthesis of Pyrroles and Dihydropyrroles from Imines: Palladium(II)‐Catalyzed Intramolecular CH Dehydrogenative Cyclization1. Issue 18 (8th April 2013) - Shi, Zhuangzhi; Suri, Mamta; Glorius, Frank
<x xml:space="preserve">Abstract</x> sp3ectacularly mild! An efficient PdII‐catalyzed intramolecular dehydrogenative cyclization of imines affords (dihydro)pyrrole products using molecular oxygen as the sole oxidant. This mild formal sp3‐CH functionalization allows rapid and atom‐economical assembly of (dihydro)pyrrole rings from inexpensive and readily available allylamines and ketones. A broad range of functional groups are tolerated.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>